Perception of using group buying sites to acquire tourist services cou-pons - Luiz Mendes Filho; Vanessa Araújo Jorge; Otávio Bezerra de Sena Júnior (Revista Brasileira de Pesquisa em Turismo, 2016)
Technologies brought new forms of business as in the case of group buying sites, which are basically a way to sell on the Internet that allows consumers to buy goods and services at lower prices. This study analyzed the travelers’ perception of the use of group buying sites to acquire tourist services coupons. The research presents a quantitative-exploratory approach using the Technology Acceptance Model to investigate the use of group buying sites to acquire tourist services coupons during a trip. They were collected 60 valid questionnaires with students from a public university in northeastern of Brazil. It was used a data collection survey type, with a non-probabilistic convenience sample. Since this is a pilot study with a small sample, the results were verified by the structural equation modeling (SEM), using the technique Partial Least Squares (PLS). From the analysis, it was found that most people who responded to the questionnaires are using group buying sites to acquire tourist services coupons. However, according to the results, the group buying sites may not be easy tools to help in decision making in purchasing tourism services.